2022
DOI: 10.1186/s10194-022-01455-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo headache in ischemic stroke patients treated with thrombectomy: a prospective study

Abstract: Background and aim Headache attributed to intracranial endovascular procedures is described in the ICHD-3. Our aim was to study the frequency and characteristics of headache specifically related to thrombectomy in patients with ischemic stroke. Methods Prospective evaluation of clinical features of headache after thrombectomy using an ad hoc questionnaire. Results One hundred seventeen patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…More PHPIS developed after IVT. Coincidently, another recanalization therapy, endovascular thrombectomy potentiated the de novo headache in ischemic stroke (Gallo et al., 2022 ). The mechanism has not been determined, but possibly due to vascular endothelial damage (Leira et al., 2002 ), ischemia‐reperfusion injury, free radicals and cytokines (Oztanir et al., 2014 ; Sladojevic et al., 2014 ), increased vascular permeability, and peripheral nerves stimulation (Ansar et al., 2014 ; Gipponi et al., 2010 ; Leira et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…More PHPIS developed after IVT. Coincidently, another recanalization therapy, endovascular thrombectomy potentiated the de novo headache in ischemic stroke (Gallo et al., 2022 ). The mechanism has not been determined, but possibly due to vascular endothelial damage (Leira et al., 2002 ), ischemia‐reperfusion injury, free radicals and cytokines (Oztanir et al., 2014 ; Sladojevic et al., 2014 ), increased vascular permeability, and peripheral nerves stimulation (Ansar et al., 2014 ; Gipponi et al., 2010 ; Leira et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…And a recent study was conducted to prospectively evaluate the clinical characteristics of headache after thrombectomy. They found nearly one-third of the patients in the study experienced de novo headache after thrombectomy [ 3 ]. However, the patient did not improve after 3 days, so headache due to endovascular therapy was excluded.…”
Section: Discussionmentioning
confidence: 99%
“…For treatments, endovascular thrombectomy potentiated de novo headaches after IS. In a study of 170 patients after thrombectomy who completed an ad hoc questionnaire, 26.5% (95% CI, 18.8-35.5%) had headaches related to the thrombectomy [16]. A prospective observational cohort study was performed in our stroke center: headaches were observed in 25.0% (138/234) of patients after ischemia, while intravenous thrombolysis (OR, 2.51; 95% CI, 1.313-4.782) increased the presence of persistent headaches attributed to IS.…”
Section: Risk Factorsmentioning
confidence: 99%